SHAXS PSIXOLOGIYASÍNDA STRESS MASHQALASÍ - Dawkeeva, A.; Saidaxmetova, X. (SCIENCE and SOCIETY, 2025)
The development of neuropsychiatric diseases associated with the physical state of the stressor, as well as the effects of various types of stress, is discussed.